2020
DOI: 10.1093/hmg/ddaa002
|View full text |Cite
|
Sign up to set email alerts
|

SPECC1L regulates palate development downstream of IRF6

Abstract: SPECC1L mutations have been identified in patients with rare atypical orofacial clefts and with syndromic cleft lip and/or palate (CL/P). These mutations cluster in the second coiled-coil and calponin homology domains of SPECC1L and severely affect the ability of SPECC1L to associate with microtubules. We previously showed that gene-trap knockout of Specc1l in mouse results in early embryonic lethality. We now present a truncation mutant mouse allele, Specc1lΔC510, that results in perinatal lethality. Specc1lΔ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…We also show that SPECC1L deficiency impaired the ability of palatal mesenchyme cells to move collectivelya result that we posit partially explains the observed delayed and abnormal palate elevation in Specc1l cGT/ΔC510 mutants (Fig. 1) 19 . The defect in collective migration was also validated in U2OS cells, an independent cell line, which strongly supports a primary role for SPECC1L in collective movement.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…We also show that SPECC1L deficiency impaired the ability of palatal mesenchyme cells to move collectivelya result that we posit partially explains the observed delayed and abnormal palate elevation in Specc1l cGT/ΔC510 mutants (Fig. 1) 19 . The defect in collective migration was also validated in U2OS cells, an independent cell line, which strongly supports a primary role for SPECC1L in collective movement.…”
Section: Discussionsupporting
confidence: 66%
“…However, palatal shelves in most mutants recover and fuse by E15.5 (Fig. 1) 19 . Analysis of E14.5 sections at mid-palate region indicated that the tongue in the mutant is usually adequately depressed, but the palatal shelves are acutely angled and do not immediately move inwards to occupy the space above the tongue (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SPECC1L cGT/ΔC510 compound mutant mice also exhibit palatal shelf elevation delay, and SPECC1L is a downstream cytoskeletal effector molecule in the palate that is regulated by the interferon regulatory transcription factor 6 (IRF6). SPECC1L regulates the palate development downstream of IRF6 29 . The collective data indicate that SPECC1L functions are necessary for normal facial morphogenesis and of its vital role in cell migration and adhesion.…”
Section: Discussionmentioning
confidence: 86%